To multiply the polynomials \((3x - 1)(2x + 4)\), we can use the distributive property (also known as the FOIL method for binomials):
- Multiply the first terms: \(3x \cdot 2x = 6x^2\)
- Multiply the outer terms: \(3x \cdot 4 = 12x\)
- Multiply the inner terms: \(-1 \cdot 2x = -2x\)
- Multiply the last terms: \(-1 \cdot 4 = -4\)
Now, combine all the terms:
\[ 6x^2 + 12x - 2x - 4 \]
Combine the like terms (\(12x\) and \(-2x\)):
\[ 6x^2 + (12x - 2x) - 4 = 6x^2 + 10x - 4 \]
So the final answer is:
\[ 6x^2 + 10x - 4 \]
In the blanks, we have:
- Blank for \(x^2\): 6
- Blank for \(x\): 10
- Blank for the constant: -4
Thus, filling in the blanks gives:
6 x^2 + 10 x + (-4)